2013
DOI: 10.1097/hjh.0b013e328364a2a1
|View full text |Cite|
|
Sign up to set email alerts
|

Moxonidine-induced central sympathoinhibition improves prognosis in rats with hypertensive heart failure

Abstract: Moxonidine-induced central sympathoinhibition attenuated brain oxidative stress, prevented cardiac dysfunction and remodelling, and improved the prognosis in rats with hypertensive heart failure. Central sympathoinhibition can be effective for the treatment of hypertensive heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
(77 reference statements)
1
16
0
2
Order By: Relevance
“…In our preliminary experiments, central infusion of yohimbine or efaroxan alone had little effect on basal BP and ROS generation in the RVLM (data not shown). As reported previously [3,30], we also confirmed that central injection of moxonidine significantly decreased BP and excretion of uNE. In this work, moxonidine reduced ROS content in a dose-dependent manner, indicating a specificity of effects of moxonidine.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our preliminary experiments, central infusion of yohimbine or efaroxan alone had little effect on basal BP and ROS generation in the RVLM (data not shown). As reported previously [3,30], we also confirmed that central injection of moxonidine significantly decreased BP and excretion of uNE. In this work, moxonidine reduced ROS content in a dose-dependent manner, indicating a specificity of effects of moxonidine.…”
Section: Discussionsupporting
confidence: 93%
“…An enhanced oxidation in the RVLM via activation of phosphoinositide-3 kinase (PI3K) signal pathway has been suggested to lead to the neurogenic hypertension [15]. Recently, it is reported that moxonidine attenuates the whole brain oxidative stress in rats with hypertensive heart failure [3]. Therefore, the goal of this study was to determine whether central antihypertensive mechanism of moxonidine is associated with anitoxidative stress in the RVLM and possible mechanism involved.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Three sections were examined per heart using a four times magnified lens for the fibrosis analysis (Honda et al. 2013). A calibrated digital camera (Model BZ-9000, Keyence Co., Osaka, Japan) and an imaging analysis program (BZH1C; Keyence Co., Tokyo, Japan) were used in the histological analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of hypertensive rats with MOX can reduce left ventricular IL-1b, TNF-a and IL-6 levels, as well as inhibit inducible nitric oxide synthase (iNOS) expression through Akt and p38 MAPK signaling pathways [26]. What's more, MOX can attenuate noradrenaline-induced cardiomyocyte apoptosis and fibroblast proliferation, and thus restrain myocardial fibrosis and ventricular remodeling [27]. These results suggested that MOX might be a potential anti-inflammatory and anti-fibrotic agent.…”
Section: Introductionmentioning
confidence: 93%